An experience sampling study on the ecological validity of the SWN-20: Indication that subjective well-being is associated with momentary affective states above and beyond psychosis susceptibility. (December 2017) - Pos, Karin; de Wit, Iris E.; van Dijk, Floor A.; Bartels-Velthuis, Agna A.; Bruggeman, Richard; Meijer, Carin J.; de Haan, Lieuwe; Alizadeh, Berhooz Z.; Bartels-Velthuis, Agna A.; Van Beveren, Nico J.; Bruggeman, Richard; Cahn, Wiepke; et al.
Abstract: Subjective well-being (SWB) is associated with treatment adherence and symptom outcome in people with psychotic disorders. Also, it is associated with psychosis susceptibility and it is partly hereditable. The SWN-20 is a widely used tool to assess subjective well-being in patients; it was also found to be suitable for assessing SWB in healthy populations. Yet it is unclear how this retrospectively measured construct may be associated with momentary affective state, which is the proposed underlying mechanism of subjective well-being. This study therefore investigated the ecological validity of the SWN-20 in people at different risk for psychosis. In 63 patients with a psychotic disorder and 61 siblings of patients with a psychotic disorder we assessed whether subjective well-being as measured with the SWN-20, was associated with momentary positive affect, negative affect, reward experience and stress-sensitivity as measured by the experience sample method (ESM). Higher subjective well-being was associated with higher momentary positive affect and lower negative affect, and this association was not conditional on psychosis vulnerability. Subjective well-being was not associated with stress-sensitivity or reward-experience. SWN-20 is an easy-to-use and ecologically valid tool to measure subjective well-being in people with different vulnerability for psychosis. Highlights: SWN-20 is an easy-to-use tool to measure subjective wellbeing. Momentary affective states associate with SWN-20. Stress-sensitivity and reward experience do not associate with SWN-20.